A different three Rs for education : reason, relationality, rhythm - Allan, George; Evans, Malcolm D. (Value inquiry book series ;, 2006)
This book of twelve essays applies the holistic theories of process philosophy to the educational challenges that teachers face in today's complexly changing world. Topics range from staff development to spirituality, exploring issues of student and teacher motivation, developmental stages of learning, imaginative thinking and writing, nourishing relationships, moral and environmental education, and the development of hospitable learning environments.